2016
DOI: 10.1136/bmjopen-2015-010134
|View full text |Cite
|
Sign up to set email alerts
|

STROBE-AMS: recommendations to optimise reporting of epidemiological studies on antimicrobial resistance and informing improvement in antimicrobial stewardship

Abstract: ObjectivesTo explore the accuracy of application of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) tool in epidemiological studies focused on the evaluation of the role of antibiotics in selecting resistance, and to derive and test an extension of STROBE to improve the suitability of the tool in evaluating the quality of reporting in these area.MethodsA three-step study was performed. First, a systematic review of the literature analysing the association between antimicrobial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 19 publications
1
61
0
1
Order By: Relevance
“…In this setting, a majority of the patients carrying 'resistant' bacteria will come from the surrounding health-care region [17,45]. The quality of evidence of ASP effects on resistance is still low [8,46]. To improve studies specifically looking at correlating antimicrobial use and resistance development, a Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) tool was developed (STROBE-AMS) [46].…”
Section: Microbiological Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, a majority of the patients carrying 'resistant' bacteria will come from the surrounding health-care region [17,45]. The quality of evidence of ASP effects on resistance is still low [8,46]. To improve studies specifically looking at correlating antimicrobial use and resistance development, a Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) tool was developed (STROBE-AMS) [46].…”
Section: Microbiological Outcome Measuresmentioning
confidence: 99%
“…The quality of evidence of ASP effects on resistance is still low [8,46]. To improve studies specifically looking at correlating antimicrobial use and resistance development, a Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) tool was developed (STROBE-AMS) [46]. Concerning SDD/SOD, there is still discussion regarding possible resistance development and it is therefore highly advisable to monitor possible resistance development when implementing such an intervention [47].…”
Section: Microbiological Outcome Measuresmentioning
confidence: 99%
“…There is evidence that successful implementation of stewardship programs in hospitals has improved antibiotic prescribing practices [76][77][78]. A number of studies that looked at the impact of antibiotic stewardship programs indicated that in spite of most studies having differing assessment tools, challenges with quality of evidence, there is consensus that it holds great promise in improving rational antibiotic prescriptions [79][80][81][82]. Majority of outcomes studies showed positive improvement in both clinical and economic outcomes for patients [76,83].…”
Section: > N = 5079mentioning
confidence: 99%
“…Subsequently, several extensions to STROBE were published, some including authors involved in the original Statement, to provide more nuanced and tailored guidance. [3][4][5][6][7][8][9][10][11][12][13][14][15] In principal, these efforts are valuable, but inconsistencies may arise because extension production is not coordinated, and there is no clear guidance on their creation.…”
Section: To the Editormentioning
confidence: 99%